Investigation of substituted 6-aminohexanoates as skin penetration enhancers - Brychtova, Katerina; Dvorakova, Lenka; Opatrilova, Radka; Raich, Ivan; Kacerova, Sandra; Placek, Lukas; Kalinowski, Danuta S; Richardson, Des R; Jampilek, Josef (Bioorganic & medicinal chemistry, 2012)
Skin penetration enhancers are compounds used to facilitate the transdermal delivery of drugs that are otherwise not sufficiently permeable. Through a synthetic route implementing two series of esters, we generated transdermal penetration enhancers by a multi-step reaction with substituted 6-aminohexanoic acid. We present the synthesis of all newly prepared compounds here with structural confirmation accomplished by (1)H NMR, (13)C NMR, IR and mass spectroscopy (MS). The lipophilicity (logk) of all compounds was determined via RP-HPLC and their hydrophobicity (logP/ClogP) was also calculated using two commercially available programs. Ab initio calculations of geometry and molecular dynamic simulations were employed to investigate the 3-dimensional structures of selected compounds. The transdermal penetration-enhancing activity of all the synthesized esters were examined in vitro and demonstrated higher enhancement ratios than oleic acid. Compounds 2e (C(10) ester chain) and 2f (C(11) ester chain) exhibited the highest enhancement ratios. It can be concluded that the series non-substituted at the C((2)) position by a ω-lactam ring showed significantly higher activity than those with azepan-2-one. None of the prepared compounds penetrated through the skin. All of the investigated agents demonstrated minimal anti-proliferative activity using the SK-N-MC neuroepithelioma cell line (IC(50)>6.25μM), suggesting these analogs would have a low cytotoxic profile when administered in vivo as chemical penetration enhancers. The correlation between the chemical structure of the studied compounds and their lipophilicity is discussed in regards to transdermal penetration-enhancing activity.
Keywords: Hydrophobic and Hydrophilic Interactions; prasata; Swine; simulace molekulární dynamiky; protinádorové látky; Caproates; aplikace lokální; Cell Line, Tumor; Stereoisomerism; hydrofobní a hydrofilní interakce; Pyrrolidines; Molecular Dynamics Simulation; pyrrolidiny; kůže; kapronáty; stereoizomerie; Animals; lidé; Aminocaproic Acid; Skin; Humans; zvířata; kyselina 6-aminokapronová; Administration, Topical; kožní absorpce; Skin Absorption; nádorové buněčné linie; Antineoplastic Agents